Ketaping Soccer School Coaching - Ridho Bahtra; Eko Putra (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2019)
The purpose of this study was to see the fostering of Ketaping Football School (SSB) in Batang Anai District, Padang Pariaman. This type of research is descriptive. The study population was all SSB Ketaping U-12 Year players. Sampling in this study with a total sampling technique, so that the sample in this study is the SSB Ketaping U-12 years, amounting to 25 people. Data were collected using a questionnaire compiled using the Guttman scale. The data analysis technique is descriptive analysis. The results of data analysis show that: 1) The description of the quality of athletes is in the Fair classification with a percentage of 75.8%. 2) Facilities and infrastructure are in sufficient classification with a percentage of 70.4%. 3) Organizations in Ketaping SSB are classified as poor with a percentage of 55.6%